IR64 NILs for partial blast resistance genes; pi21(BC5F5), Pi35(BC2F5), and Pb1(BC6F5). - CGIAR Research Program on Rice (2021)
Completion of the development of IR 64 NILs for partial blast resistance genes; pi21(BC5F5), Pi35(BC2F5), and Pb1(BC6F5).